PENELITIAN HASIL BELAJAR MATEMATIKA DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION DAN PROBLEM BASED LEARNING DITINJAU DARI MOTIVASI SISWA KELAS XI IPA SEKOLAH MENENGAH ATAS - Fitriana, Dyah Ayu (Jurnal Studi Islam dan Sosial, 2023)
This research aims to determine: (1) the influence of the Realistic Mathematic Education and Problem Based Learning learning approaches. (2) the influence of learning motivation on learning outcomes. (3) the interaction between Realistic Mathematical Education and Problem Based Learning learning approaches in terms of learning motivation on mathematics learning outcomes. Type of quantitative research with experimental design. The research sample used Cluster Random Sampling from the population of class XI Science students at SMA Muhammadiyah 1 Surakarta in 2016/2017. Data collection techniques using questionnaires, tests and documentation. Before the analysis is carried out, a balance test, normality test and homogeneity test are first carried out. Data analysis technique using two-way unequal cell variance analysis with a significance level of 5%. The results of this research were: (1) there is an influence of learning approaches on mathematics learning outcomes. (2) there is an influence of learning motivation on mathematics learning outcomes. (3) there is no interaction between learning approach and learning motivation on mathematics learning outcomes